ShuntScope-Guided Versus Free-Hand Technique for Ventricular Catheter Placement: A Retrospective Comparative Study of Intraventricular Catheter Tip Position and Complication Rate - Issa, Mohammed; Nofal, Mohammed; Miotk, Nikolai; Seitz, Angelika; Unterberg, Andreas; El Damaty, Ahmed (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background The position of the ventricular catheter (VC) is essential for a proper function of cerebrospinal fluid diversion system. A ShuntScope-guided (SG) method might be helpful in reducing complications. The purpose of this study is to compare the accuracy of catheter placement and the complication and revision rates between SG and free-hand (FH) techniques.Methods This is a retrospective study based on a prospectively acquired database of patients who underwent VC placement between September 2018 and July 2021. Accuracy of catheter placement was graded on postoperative imaging using the 3-point Hayhurst grading system. Complication and revision rates were documented and compared between both groups with an average follow-up period of 20.84 months.Results Fifty-seven patients were included. The SG technique was used in 29 patients (mean age was 6.3 years, 1.4–27.7 years, 48.1% females), and the FH technique was used in 28 patients (mean age was 26.7 years, 0.83–79.5 years, 67.9% female). The success rate for the optimal placement of the VC with grade I on the Hayhurst scale was significantly higher in the SG group (93.1%) than in the FH group (60.7%), p = 0.012. The revision rate was higher in the FH group with 35.7% versus 20.7% in the SG group, p = 0.211.Conclusion VC placement using the SG technique is a safe and effective procedure, which enabled a significantly higher success rate and lower revision and complication rate. Accordingly, we recommend using the SG technique especially in patients with difficult anatomy.
Keywords: CSF; free-hand; hydrocephalus; shunt system; ventricular catheter